EXAMINATION OF CONSUMPTION HABITS OF THE VIEWERS AND NATIONAL ECONOMY EFFECT AT THE 2023. WKF KARATE WORLD CHAMPIONSHIP - Bátor, Gábor László; Laczkó, Tamás; Szabó, Péter (Stadium - Hungarian Journal of Sport Sciences, 2024)
Sporting event tourism is a rapidly expanding segment of sports tourism (DREYER, 2002; WEED, 2006; BÁNHIDI, 2015; BORBÉLY-MÜLLER, 2015; LAFLIN, 2018). Alongside the growing number of events, domestic and international spectators have also increased significantly (LAFLIN 2018, LACZKÓ-STOCKER, 2020). Hungary hosted the Karate World Championship for the first time in karate history. This study aimed to analyze the consumption habits of domestic and international spectators attending the event.A questionnaire survey of 806 visitors was conducted, and the data was analyzed using SPSS. Economic impacts were assessed using input-output analysis based on the Sectoral Balance of Relations. Results indicated that the event's tourism appeal was primarily local and regional, with 78.7% of domestic respondents traveling less than 50 km. Domestic spectators attended an average of 2.76 competition days during the six-day event, while international visitors spent 4.42 nights in Hungary. The average total expenditures were HUF 43,075.26 for domestic spectators and HUF 471,741 for international spectators. The event contributed HUF 1.55 billion to Hungary's GDP. The World Championship reinforced Hungary's status in sports tourism, showcasing the economic and social benefits of hosting international events. Positive feedback from spectators affirmed the successful organization and highlighted the continued viability of such events in Hungary.